The monkey-rope a psychotherapist's reflections on relationships - Lewis, Jerry M. (Bernel Books, 1996)
The Monkey-Rope is Melville's symbol in his novel Moby Dick for the relationships that bind each of us to every other individual who shares our human condition - family, friends, lovers, colleagues at work, and all those who make up the society and world around us